Indian Orchid Trade - a Critical Review - Chakrabarti, Kalyan (Indian Forester, 1995)
A critical and systematic analysis has been made of orchid export data from 1983 to April 1992 and its domestic orchid trade and presented in the paper. Principal genera involved in orchid export include Pleione, Dendrobium, Cypripedium, Paphiopedilum, Coelogyne, Cymbidium, Phalaenopsis, Vanda, Calanthe, Aerides etc. and principal importing countries of Indian orchids are Japan, United States of America, Great Britain, Netherlands, Federal Republic of Germany etc. While the genus Pleione is predominantly exported to Japan, the genus Dendrobium is predominantly exported to United States of America as these orchid genera are seemingly in greater demand to those countries in comparison to other orchid genera. Quantitative figures of orchid exports from India to various countries are elucidated in the paper genera and countrywise. The analysis of data indicates positive correlation amongst specific importing countries with some particular orchid genera as well. The problems of orchid cultivation along with suitable recommendations have also been highlighted in the paper, which include resorting to modern scientific orchid culture techniques involving tissue and meristem culture amongst others.